Độ đo Hausdorff của tập Semi-Đại số được định nghĩa bởi các đa thức bậc <=2 - Phan, Phiến (Trường Đại học Đà Lạt, 2012)
In this paper we compare two bounds of Hausdorff measure of semi-algebraic sets which proved by Ta Le Loi and Phan Phien (see[L-P1] and [L-P2]).